Bridging Cultures and Languages: Pedagogical Strategies for Local Language Use in EFL Learning - Rahayu, Arum Putri (Proceeding of International Conference on Islamic Education (ICIED), 2025)
This qualitative case study investigates the implementation of multicultural-based English teaching in ninth-grade speaking classes at SMP Al Falah Jogorogo, involving ten teacher and student participants. Data were collected through classroom observations, interviews, and analysis of speaking materials. The findings show that tasks built around local traditions such as regional foods, festivals, and greetings, combined with global themes, make speaking activities meaningful, increase motivation and engagement, and help students feel less anxious, speak in longer stretches, and participate more actively. However, inconsistent classroom language policy, limited English exposure, and habitual alternation into Indonesian and Javanese reduce opportunities for sustained English use, increase cognitive load, and slow language development. Multicultural-based materials support gradual gains in vocabulary, fluency, and cultural awareness when accompanied by teacher modelling, group work, and space for students to draw on their cultural experiences. The study argues that culturally responsive EFL pedagogy in multilingual rural contexts requires explicit language-use guidelines, purposeful bilingual scaffolding, and systematically designed multicultural speaking materials. These insights offer a situated example of how multicultural principles can be operationalized in junior high school EFL classrooms and point to the need for further practice-oriented research on material design and classroom language management in Indonesia.